PENINGKATAN KOMPETENSI SISWA SEKOLAH MENENGAH PERTAMA NEGERI 1 SIMPANG MAMPLAM BERSAMA KAMPUS MENGAJAR - Nabiela Dzakiaturrahmah; Washurachim Safitri; Winda Ramadianti (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The Teaching Campus Program is one of the Merdeka Belajar Kampus Merdeka (MBKM) programs designed by the Ministry of Education and Culture of the Republic of Indonesia (Kemendikbud) and supported by the Education Fund Management Institute (LPDP) of the Ministry of Finance. This activity starts from January 29 to June 29, 2022. SMP Negeri 1 Simpang Mamplam is located on Jl. Banda Aceh – Medan, Simpang Mamplam District, Meunasah Mesjid, Simpang Mamplam District, Bireuen Regency, Aceh Province, this school provides a moving class model that makes it easier for teachers and students, the curriculum used is a prototype curriculum or independent curriculum with the number of students from grades 7-8 approximately 324 students with 11 rombels. In this semester, all students went to school fully offline after 2 years of online learning due to the pandemic. The Teaching Campus Program aims to assist schools in terms of administration, literacy, numeracy, and technology adaptation. Students assist teachers in working on school administration such as revising the curriculum or printing syllabuses and lesson plans, creating live dispensaries in school gardens, updating the contents of madding and training on school social media processing. For literacy and numeracy activities, students apply digital reading activities to students, through belajar.id accounts and learning houses. In terms of technology adaptation, students carry out training on the use of various types of Microssoft Office, training on the use of learning media such as the use of Youtube videos or materials derived from the internet